Leluhur Orang Nias dalam Cerita-cerita Lisan Nias - Afif, Afthonul (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This article aims to describe the origins of Nias peopleancestor based on anonymous stories (called hoho in Nias term)which were inter-generational inherited in Nias society. Generally,Nias people recognised three kinds of hoho that were always andcorrectly related to the creatures assumed as their ancestor: onombela, nadaoya, and lani ewÃ¶na. These anonymous stories have beenbecoming a buffer for the existence of Nias Culture which weremanifested on the custom ceremonies practice by Nias people untilnowadays such as mangani binu and stone jumping. In the otherhand, this article also tries to identify and describe the functionsof those rituals toward the daily life of Nias people. According tothe culture theory by van Peursen, this article proposes that therituals have three kinds functions for Nias society. First, it couldbe a means for human to deal with the supra-natural power.Second, it could be a current guarantee that humansâ effort in theirhistorical life will be a never ending process and repeatablesuccess. Third, it was related to the taboo that was existed in certaincommunity which is in fact, able to maintain the harmony ofhuman life.